(untitled) (CAHIERS MAGELLANES-NS, 2024)
The concept of Green Finance practices defines that socio-economic inclusion is essential to India's sustainable development. Governments and authorities are concentrating more on global warming and climate change, thus enabling businesses to work in innovative Green Finance practices. The evolution of Green Finance is a deliberate move to achieve the United Nations Sustainable Development Goals (UN SDGs) which promote technological innovations, focus financial support for green projects, and accelerate the greener revolution of India. Therefore, Green Finance practices are being implemented to attain sustainability in the nation. To better understand how Green Innovation and Green Finance practices act as a spark for India’s sustainability, this paper aims to present a thematic review of these concepts. This thematic evaluation consists of 77 scholarly publications from the Scopus and Web of Sciences databases, seven themes were found: 1) Green Finance and Innovation in the financial sector, 2) Green Finance for Environmental Protection, 3) Green Finance investments 4) Green Finance practices for Sustainability, 5) Green Finance for Economic Development, 6) Green Finance Policy and 7) Trends and Future directions of Green Finance are all discussed. As a result, this thematic review paper makes a significant addition to exploring inclusive green finance and green innovation, which shows that green finance greatly contributes to green innovation.